Laundry services for people with disabilities / Siti Nur Ahlia Rashid … [et al.] - Rashid, Siti Nur Ahlia; Mohamad Faizal, Balqis Damia Dhuha; Zairullail, Meor Muhammad Zaid; Mansor, Muhammad Alif Imran; Nor Azman, Nor Adistiqna; Dedy Chandra, Nur Dina Iman; Juhari, Joeaiza (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
GentleCare Laundry Co. is a business that provides services, especially for people with special needs. The main problem that gives us the idea to provide this kind of services is we do know that people with disabilities find it hard to do the laundry on their own. Our company idea aims to assist and support not just citizens but also individuals with disabilities such as people with wheelchairs, blind people, and more. We decided to do some innovations for our laundry that can help people with disabilities to do their laundry easily. Suitable with our motto which is gentle and care, represents how we are concerned and want to help this group of people. The first innovation is we created a ramp in front of our laundry for those people with wheelchairs. The second innovation is we provide assistants who will help people who need to do their laundry. These include implementing features such as easy-to-reach machine controls, and ergonomic design considerations to make the laundry process more manageable for individuals with mobility challenges. By providing these innovations, we are sure that we can achieve our goals of helping people with disabilities.